Design development of SOI based biologically sensitive field-effect transistor (Bio-FET) for earlier detection of cancer cell - Foo, Kai Loong; Uda, Hashim, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.